Eco-hotels as an example of environmental responsibility and innovation in savings in the hotel industry - Kostić, Marija; Ratković, Milica; Forlani, Fabio (Hotel and Tourism Management, 2019)
Green hotels are ecological buildings whose managers set up programs to save water and energy, and reduce solid waste, thereby saving money and aiding preservation of the environment. These hotels have guidelines so that the guests can stay in a safe, non-toxic and energy-efficient lodging. Green hotels are introducing environmental standards and use elements of environmentally friendly new technologies, thereby making a significant contribution to the protection of the environment and achieving better operational results. Looking at global trends in green tourism and hospitality, caused by turbulent development and carrying many negative consequences, the purpose of this paper is to point out and affirm the advantages provided by the green hotels. It also suggests that Serbia can become a more competitive destination considering its potential and resources.